Pressures on manufacturing industry to practice green supply chain management in Malaysia - Yusuf, Muhammad Fakhrul; Ramle, Rashidah; Abdullah, Norhazirawani (Springer, 2022)
Green Supply Chain Management (GSCM) has received increasing attention, at least in recent decades. During this time, it has become apparent that are significant complexities in its management. From both a practical and research perspective, there is a need to simplify and understand this complexity. To further deepen the understanding of the problem, institutional theory, which consists of three institutional pressures, namely government pressure (coercive pressure), market pressure (normative pressure) and competitive pressure (mimetic pressure), was used to investigate the relationship between institutional pressure and GSCM practices in the manufacturing industry in Malaysia. Data were collected using questionnaires in different Malaysian manufacturing companies. The hypotheses were tested using SmartPLS 3. The results from the 118 respondents showed that the command and control instrument and competitive pressure supported the hypothesis, while the economic incentives instrument and market pressure did not support the hypothesis. Finally, the enactment of stringent environmental regulations by the government was found to be most effective in promoting the adoption of GSCM practices.